Qualidade de sono e qualidade de vida em trabalhadores submetidos a diferentes esquemas de trabalho de uma empresa petroquímica - Almondes, Katie Moraes de (2007)
One of the largest problems of the present time resulting from the economic globalization and the modern technology, of the point of view of the biological rhytms of our organism, it is offering services and production of goods available in 24 o'clock, that it demands organized workers in several work schedules besides the hours of the day. Those schedules cause a series of biopsychosocial consequences in the worker's health, in function of circadian, homeostatic and psychosocial alterations. Accordingly, the aim of this study was to accomplish an evaluation of the effects of several works schedules in the pattern of the sleep wake cycle, anxiety, stress and in the health. We counted with a sample of 274 workers subdivided in 49 daytime worker groups and 225 workers in different shift work schedules with different speeds (rotating shift group, slower day shift group, faster day shift group). From the results analysis it is verified irregularities of the daily activities, stress and alterations in the workers' health in all schedules. It was also verified thata the workers thata presented irregularities in the daily activities were the mroe stressed. On the other hand, the shift works were considered more ansious and associated with bad sleep quality. It was verified that the workers with bad sleep quality were those presented larger levels of dispocional anxiety. There was no statistically significant correlation between bad sleep quality and irregular daily lifestyle. However, it can be affirmed thata shift work schendules doesn't are the main determinant for the circadian alterations, but the answers of the individuals to the shifts work; and that the inadequate behavioural strategies to work with the effects of the shift schedules. In conclusion, individual strategies related to the coping of the work in shift (adaptation and tolerance) should be extolled as indispensable tool in the ergonomic evaluation of the work